PENERAPAN AKAD MURABAHAH TERHADAP PRODUK PEMBIAYAAN KPR iB BAROKAH DI BANK JATIM SYARIAH CABANG KEDIRI - Nisrina Fajarria Nada (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
The development of islamic banking in indonesia is a manifestation of the desire of the people who need banks that can provide sound financial services that are guided by sharia principles. In this economic develoment activities, a very important sector that can support success in this achievement is the financial sector. One of them is the bank jatim sharia the kediri branch, which provides financing for people who want to own a house, namely by financing KPR Ib barokah. KPR Ib barokah is a short term financing medium or long term. The purpose of this study is to find out the mechanism of the Ib barokah mortgage financing and whether it is in accordance eith sharia principles. The formulation of the problem taken about how the Ib barokah mortgage financing mechanism and whether the murabahah contract in the Ib barokah mortgage is in accordance with sharia principles. Judging from the result of this study the mechanism is very easy and the conditions that must be met are not complicated and in term of the principles that are carried out, they are in accordance with sharia.